(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A self-organized mobile node wireless network without fixed infrastructure is mobile ad hoc network (referred MANET). Decentralization is practise of transferring power from one single master node to all other nodes. In order to remove such security threats as eavesdropping, monitoring, denial of service and routing attacks, this is achieved. Decentralization is ensured by the use of secret sharing techniques. MANET has a hidden key/public key pair that provides the public and every node with share of secret key. Nodes are spread across networkcausinga fast and unpredictable shift in its topology. New nodes can be connected to the network, while other nodes can (temporarily) exit or simply fail to connect at the same time as they move to the area not served by the network. A new node may approach other nodes to collect its confidential information and in particular, its share. Based on the type of scenario in which these keys are used, individual secret / public keys can be received. The first is popular PKI scenario: each node would independently generate its hidden / public key pairs. In order to jointly calculate a valid certificate binding node’s identity to a public key, the node must then contact other nodes. This is where we use Elliptic Curve Digital Signature Algorithm (ECDSA).